2018
DOI: 10.1186/s12883-018-1171-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel coils versus bare platinum coils for the endovascular treatment of intracranial aneurysms: a meta-analysis of randomized controlled trials

Abstract: BackgroundRecent studies have shown conflicting results regarding the effect of hydrogel coils for treating intracranial aneurysm compared to bare platinum coils. We implemented a meta-analysis to assess the value of hydrogel coils in intracranial aneurysm treatment.MethodsThe MEDLINE, EMBASE, and Cochrane Library databases were searched for randomized controlled trials (RCTs) which had evaluated hydrogel coils versus bare platinum coils for intracranial aneurysms.ResultsWe pooled 1526 patients from 4 RCTs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Consistent with the results of a current meta-analysis, 6 our study provides evidence that HSC are more efficient in treating large and giant aneurysm with better mid-term outcomes when compared with BPC. Our overall treatment results are also matching with published data of four randomized controlled trials 7 10 and three registries 11 13 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results of a current meta-analysis, 6 our study provides evidence that HSC are more efficient in treating large and giant aneurysm with better mid-term outcomes when compared with BPC. Our overall treatment results are also matching with published data of four randomized controlled trials 7 10 and three registries 11 13 .…”
Section: Discussionsupporting
confidence: 91%
“…Endovascular techniques for intracranial aneurysm (IA) repair have evolved quickly over the past decades. So far only a few of the novel techniques have been investigated in prospective trials [1,2]. Most novel devices have not been studied in large prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, other clinical trials, including the Patients Prone to Recurrence After Endovascular Treatment (PRET) trial, have demonstrated that hydrogel-coated coils do not provide improved clinical outcomes when compared to bare coils [24]. Overall, the meta-analysis of the performance of hydrogel coils demonstrated that the second-generation hydrogel coils (HydroSoft) might improve residual aneurysm and midterm recurrence, but do not exhibit any other significant differences to the traditional GDC coiling [25].…”
Section: Hydrogel-coated Coilsmentioning
confidence: 97%